The Outcome of Planned Breech Vaginal Delivery among Obstetrics Patients Presenting at Tertiary Care Hospital, Karachi - Priya Partab, Aneela Habib, Gulfishan Tariq, Urooj Naz, Sana Shameer, Sarah Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Vaginal breech delivery (VBD) is known to be associated with more perinatal and maternal complications. The safest mode of delivery in case of breech presentation has long been a debate in obstetrics. Selective vaginal breech deliveries, proper technique of breech delivery, rigorous intrapartum monitoring and presence of experienced obstetrician and pediatricians are most important factors for good outcome in vaginal breech delivery without affecting the maternal and fetal well-being and helps in decreasing the caesarean section rate. Very few studies on the subject have been carried out in poor-resource settings. The aim of the study was to determine the outcome of planned breech vaginal delivery among obstetrics patients presenting at Tertiary Care Hospital, Karachi. Study Design: This Cross sectional study was conducted at Department of Gynaecology and Obstetrics, Civil Hospital, Karachi for the duration of Six months from November, 2019 to May, 2020. Subjects and Methods: Data was prospectively collected from patients after taking a verbal consent. 89 pregnant who met the diagnostic criteria were included. Quantitative data was presented as simple descriptive statistics giving mean and standard deviation and qualitative variables was presented as frequency and percentages. Effect modifiers were controlled through stratification to see the effect of these on the outcome variable. Post stratification chi square test was applied taking p-value of ≤0.05 as significant. Results: A total of 89 patients were included in this study. Mean age, gestational age and duration of labour in our study was 31.78±2.81 years, 37.72±1.58 weeks and 10.72±1.56 hours. Out of 89 patients, 11.2%, 23.6%, 12.4% neonates had had APGAR score < 7, NICU admission and brachial plexus injury. Conclusion: Vaginal delivery of term breech fetus is a safe option in a carefully selected group of women. Pre-delivery assessment, vigilant labour monitoring and delivery by trained doctors can minimize poor feto-maternal outcome.